Students’ Perceptions on the Implementation of Blended Learning in English for Mathematics - Susanti Malasari; Lemmuela Alvita Kurniawati; Ika Fathin Resti Martanti (Metathesis: Journal of English Language, Literature, and Teaching, 2020)
AbstractCovid-19 Pandemic has changed the teaching and learning processes of all education levels from offline classroom into online classroom. This situation forces all schools and universities to be familiar with blended learning. It is such an advantage for Universities that have already implemented blended learning in their teaching and learning processes. The full implementation of blended learning raises various perceptions from both lecturer and students. This study employed a qualitative research method to investigate the students’ perceptions on the implementation of blended learning in English for Mathematics. This study was conducted by using a qualitative method to investigate the students’ voices on the implementation of blended learning in English for Mathematics class. Six student participants who attended English for Mathematics in English Language Education Department of a state university were involved in this study. To gather the data, the researchers conducted an interview with the participants at the end of the semester. The interview was conducted in a Focus Group Discussion (FGD) session. It is found that most students have positive perceptions toward the implementation of blended learning in their teaching and learning processes. The participants stated that the implementation of blended learning in their class facilitates students to deepen their understanding about the materials, blended learning promotes independent learning, and blended learning enables students to experience various kinds of learning media.